Pengembangan Filamen 3D Printing dari Strip Sampah Plastik Polyethylene Terephthalate Daur Ulang - Muhammad Ali Chandra; Muh. Farid Hidayat (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Polyethylene Terephthalate (PET) plastic waste is one of the most common types of waste whose volume continues to increase and poses a significant threat to the environment. This study aims to develop 3D printing filament from recycled PET bottle strips and evaluate the effect of printing parameters on the quality of printed parts produced using Fused Deposition Modeling (FDM) technology. An experimental method was employed, consisting of cleaning, drying, cutting PET bottles into strips measuring 8–12 mm, filament extrusion at a temperature of 220°C, and specimen printing using nozzle temperature variations of 255°C, 265°C, 275°C, and 285°C, combined with bed temperatures of 50°C and 70°C. The results showed that the produced filament had a diameter ranging from 1.65 to 1.80 mm, which is close to the standard diameter of commercial filament (1.75 mm). The quality of the printed parts was influenced by the combination of nozzle and bed temperatures.